Electrochemical verification of the redox mechanism of FeS2 in a rechargeable lithium battery. (10th September 2015) - Zhang, Sheng S.; Tran, Dat T.
Highlights: Redox mechanism of FeS2 is studied by galvanostatic cycling and impedance analysis. FeS2 cannot be re-constituted by recharge once being fully discharged. Li/FeS2 battery converts into a hybrid of a Li/FeS cell and a Li/S cell in the first discharge. Li/FeS2 battery faces the same problems with Li/S battery in relation to the dissolution of polysulfide. Abstract: The redox mechanism of micro-sized FeS2 particles in a rechargeable lithium battery is studied by galvanostatic cycling and ac-impedance analysis. It is shown that FeS2 is irreversibly reduced on the first discharge, turning Li/FeS2 cell into a combination of Li/FeS and Li/S chemistries, as suggested by two distinct discharge plateaus at ∼1.5 and 2.0 V, respectively. The first discharge consists of an irreversible conversion of FeS2 to Li2 FeS2 intermediate and its subsequent reduction to metallic Fe and Li2 S. The first discharge suffers an initial voltage delay, suggesting that the discharge progresses in a thermodynamic non-equilibrium condition. The initial voltage delay can be attributed to the large grain boundary resistance (GBR) of pristine FeS2 particles, which impedes the nucleation of a new solid Li2 FeS2 phase causing high polarization. Ac-impedance spectra of the FeS2 cathode are composed of a semicircle and a straight sloping line, representative of an electrode reaction resistance (Rer ) and a Li + adsorption impedance, respectively. The Rer is found to decrease progressively during the first discharge and reaches a plateau when the cell is charged above 2.5 V vs. Li/Li +, being consistent with the model that FeS2 is irreversibly reduced during the first discharge and that the Li2 S/Li2 Sn redox couple is formed in recharge. It is indicated that Li/FeS2 batteries face the same problems as Li/S batteries, such as the dissolution of lithium polysulfide, the formation of a redox shuttle, and the loss of sulfur active material.